2000
DOI: 10.1074/jbc.275.13.9106
|View full text |Cite
|
Sign up to set email alerts
|

The Akt Proto-oncogene Links Ras to Pak and Cell Survival Signals

Abstract: The Ras oncogene regulates cellular proliferation, differentiation, transformation, and survival through multiple downstream signals. Ras signals through its effector phosphoinositide 3 (PI3) kinase to the Pak protein kinase (p65 pak ), but the steps from Ras to Pak remain to be elucidated. PI3 kinase can stimulate the small G protein, Rac, a direct activator of Pak, as well as the Akt proto-oncogene, a serine-threonine protein kinase. We found that activated Akt stimulated Pak, whereas a dominant negative Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
178
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(190 citation statements)
references
References 32 publications
(17 reference statements)
7
178
3
Order By: Relevance
“…It has been reported that activation of MEK/ERK leads to phosphorylation of MITF at serine 73, resulting in its degradation [28,38] . The PI3K⁄Akt pathway plays an important role in cell growth regulation and apoptosis inhibition [39,40] . In addition, activation of the PI3K⁄Akt pathway reduces tyrosinase transcription and melanogenesis in B16F10 cells [17,29] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of MEK/ERK leads to phosphorylation of MITF at serine 73, resulting in its degradation [28,38] . The PI3K⁄Akt pathway plays an important role in cell growth regulation and apoptosis inhibition [39,40] . In addition, activation of the PI3K⁄Akt pathway reduces tyrosinase transcription and melanogenesis in B16F10 cells [17,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids, DNA transfection, cell culture and MTT assay The dominant negative PAK-1 plasmid, the K299R mutant, and the vector control, were gifts from Dr Jefferey Field (Sells et al, 1997;Tang et al, 2000). DNA transfection was performed using Lipofectamine (Invitrogen Life Technology) according to the manufacturer's instructions.…”
Section: Body Weights and Intraperitoneal Glucose Tolerance Testmentioning
confidence: 99%
“…The effects of US3 on the actin cytoskeleton have recently been attributed to an interaction of US3 with p21-activated kinases (PAKs) 1 and 2, and extracellular PRV virus titres were reduced in PAK2 2/2 cells (Van den Broeke et al, 2009b). Interestingly, PAKs are not only involved in rearrangements of the actin cytoskeleton, but also in anti-apoptotic effects (Cotteret et al, 2003;Gnesutta et al, 2001;Jakobi et al, 2001;Rudel & Bokoch, 1997;Schurmann et al, 2000;Tang et al, 2000). Based on our current study, we hypothesize that the reduced PRV titres on PAK2 2/2 cells are probably due to the effect of PAK2 on the actin cytoskeleton, rather than the effect of PAK2 on apoptosis.…”
mentioning
confidence: 99%